The effects of armed conflict on schooling in Sub-Saharan Africa - (:unkn) unknown (My University, 2011)
In the past decades, most of the countries in sub-Saharan Africa have been affected by armed conflicts. By means of a time-series cross-sectional (TSCS) database, we attempt to measure the impact of war on a sample of 43 countries in Africa from 1950 to 2010. These conflicts, and especially civil wars, are shown to have a strong negative effect on the educational performances of the countries studied. The rate of children not attending school, as well as secondary school enrollment rates, seems particularly sensitive to periods of conflict. It also appears that government expenditures in social sectors including education are a positive factor in increasing school enrollment. In contrast, military expenditure is significantly and inversely related to schooling opportunities. Thus, if but 1 % of the GDP were allocated to education expenditure, the rate of children not attending school would decrease by 1.6 % and the secondary school enrollment rate would increase by 2.2 %.
Keywords: African Research